Film sebagai Media Social Marketing: Yasmin Ahmad Berjualan Ide Multikulturalisme - Syaukat, Rosidah; Imanjaya, Ekky (Bina Nusantara University, 2011)
Film is a message disseminating media and also mass communication tool. This statement sometimes appears when we are in film study. Film, and media in general, could be an effective propaganda. As a media, film could be used as a media to promote community awareness towards goodness issues. The question is how far we could consider film as one media to social marketing? The article discusses whether we could consider film as social marketing media. If it could be considered, what kind of films and how. Researcher took case study of Yasmin Ahmad’s films, Malaysian’s director, to analyze social marketing inside. All Yasmin’s films that could be analyzed in this research consist of multiculturalism issue, covered by love story or family issues. Hopefully this article is becoming a beginning study so other researchers could analyze films and film-makers in Indonesia.